ScAuIn – a new representative of the RAuIn series - Romaka, V. V.; Amigó, María Lourdes; Franco, Diego Gaspar; Corredor, L. T.; Wurmehl, S.; Büchner, B.; Seiro, S. (Academic Press Inc Elsevier Science, 2022)
Fil: Romaka, V. V.. Leibniz Institute for Solid State and Materials Research; Alemania